A 2D porphyrin-based covalent organic framework with TEMPO for cooperative photocatalysis in selective aerobic oxidation of sulfides. (2nd February 2021) - Feng, Keyu; Hao, Huimin; Huang, Fengwei; Lang, Xianjun; Wang, Cheng
Abstract : This work reports the cooperative photocatalysis of a two-dimensional covalent organic framework with an electron transfer mediator in a selective organic transformation. Abstract : Two-dimensional covalent organic frameworks (2D COFs) have received increasing attention in photocatalysis recently. Merging their photocatalytic process with an additional redox mediator could improve the corresponding chemical conversion efficiency, leading to an interesting cooperative behaviour. Herein, we report the photocatalytic performance of a 2D imine-linked porphyrin-based COF (Por-COF) with (2, 2, 6, 6-tetramethylpiperidin-1-yl)oxyl (TEMPO) in a selective organic transformation. After being irradiated with white light-emitting diodes, Por-COF showed moderate activity in selective aerobic oxidation of sulfides. Interestingly, by using TEMPO as an electron transfer mediator, the photocatalytic efficiency could be significantly improved, due to a paradigm of cooperative photocatalysis between Por-COF and TEMPO. This work foreshadows that 2D COFs can provide a unique platform to construct cooperative photocatalysts with a redox mediator.